Characterization Aluminum Spot Welding with Mesh Variations of Copper Powder Added on 40, 50, and 60 Meshing - Pramuko Ilmu Purboputro; Patna Partono (Engineering Proceedings, 2025)
This study aims to determine the effect of adding copper powder with different mesh sizes on the welding point, as well as the resulting tensile strength, micro photo and hardness. The raw material of this research is aluminum type 1100. The tests included tensile strength tests (ASME QW-4629 standard), micro photo tests with a metallographic microscope, and Vickers tests (AWS D8.9-97 standard). The results of the tensile strength test rank mesh 40 (556.38), mesh 50 (739.13) and mesh 60 (1316.10) in descending order of tensile strength. The highest value of hardness is in the fusion zone (nugget). The last heat affected zone is in the base metal area and the order of hardness is, in descending order, mesh size 60, 50, and lastly, 40. For micro images, all of the results obtained are the same because they use the same material. The widest melted area in the welding area is on the 60 mesh and it decreases proportionally with the larger meshes.